Revitalisasi Manuskrip Islam Mempawah melalui Workshop Literasi Arab Melayu Pada Siswa MA Al-Mansyuri - Erwin Mahrus; Maulidah Rahmah; Winia Hade Saputri; Aqila Fitriani Ulayya; Derry Indhie Bhakti; Feti Ayu Pratarti; Munawir Hasan (Irajagaddhita, 2026)
Arabic–Malay script is one of the intellectual heritages of Islam that has played an important role in the development of Islamic literacy in the Indonesian archipelago. However, the ability to read this script among the younger generation has been steadily declining, including in Mempawah Regency, which possesses numerous manuscripts by local Islamic scholars. This community service program aims to revitalize Arabic–Malay literacy skills through the implementation of an Arabic–Malay Literacy Workshop for students of MA Al-Manshury Mempawah. The method employed is Participatory Action Research (PAR), which actively involves students in the processes of problem identification, workshop implementation, and outcome evaluation. The activities include an introduction to the history of the Arabic–Malay script, training in basic letters, and practical reading exercises using the manuscript Aqāʾid al-Īmān by Abdul Qadir bin Ahmad Al-Banjari. Pretest–posttest results indicate a significant improvement in students’ Arabic–Malay reading abilities, with an average pretest score of 56.60 and a posttest score of 79.20, as well as paired-sample t-test results (p < 0.05). These findings demonstrate that the workshop was effective in enhancing Arabic–Malay literacy competencies and in opening students’ access to the local Islamic intellectual tradition. This program underscores the importance of revitalizing the Arabic–Malay script as part of preserving Islamic literacy culture and strengthening the scholarly identity of the Malay community in West Kalimantan.